A Novel Optical Fiber Temperature Sensor Based on Fabry‐Perot Cavity. Issue 10 (26th July 2013) - Zhao, Yong; Wang, Dan; Lv, Riqing
ABSTRACT A novel fiber optic Fabry‐Perot (F‐P) temperature sensor has been developed based on anhydrous ethanol as the sensitive medium in the cavity. The theory and principle of the novel fiber optic F‐P sensor are presented. In this article, the temperature‐sensitive property of anhydrous ethanol was studied by experiments, and it could archive a good linearity relative to the temperature. Then, anhydrous ethanol was filled in the cavity of F‐P sensor as the sensitive medium. With the property of the temperature‐controlled refractive index, the properties of the novel fiber optic F‐P temperature sensor were studied through the experiments. The fiber optic F‐P sensing probe was fabricated and the experiments were carried out to prove the feasibility of the temperature measurement. And, it obtained a sensitivity of 1.56 nm/°C when the cavity length was 80.1 µm. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2487–2490, 2013